Application of QuEChERS for Determining Xenobiotics in Foods of Animal Origin - Coralia V. Garcia; Ahmed Gotah (Journal of Analytical Methods in Chemistry)
The use of pesticides and veterinary drugs results in the appearance of residues of xenobiotics in foods. Thus, several methods have been developed for monitoring them; however, most are tedious and expensive. By contrast, the QuEChERS (Quick, Easy, Cheap, Effective, Rugged, and Safe) methodology involves a microextraction that yields small samples and has been applied for the analysis of various xenobiotics including pesticides, antibiotics, and mycotoxins. QuEChERS has shown advantages over other techniques including fast sample preparation, reduced needs for reagents and labware, and versatility. This approach allows the simultaneous determination of pesticides with various polarities and volatilities and can be easily modified for the analysis of a wide range of xenobiotics in various matrices including animal products rich in fat. Nevertheless, to attain high recoveries, the extraction, cleanup, and concentration steps have to be optimized according to the target compounds and matrix. Hence, QuEChERS is a promising and environmentally friendly methodology for the high-throughput routine analysis of xenobiotics in animal products. This review focuses on the application of QuEChERS to foods of animal origin and describes recent developments for the optimization of the analysis of veterinary drugs, pesticides, polycyclic aromatic hydrocarbons, and other compounds of concern.